APA Handbook of Men and Masculinities. 2016
DOI: 10.1037/14594-025
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and male socialization.

Abstract: This chapter reviews scientific theory and research on pornography consumption and male socialization. The term pornography is often used pejoratively. Consistent with our prior work (e.g., Wright & Bae, 2013;Wright, Malamuth, & Donnerstein, 2012), we use the term only as shorthand for mediated content depicting nudity and explicit sexual acts. No evaluative connotation is implied. 1 The voluminous nature of the pornography literature necessitates the adoption of certain chapter parameters. We focus on quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 112 publications
1
26
0
4
Order By: Relevance
“…Furthermore, a greater frequency of pornography use was predictive of greater agreement with the statement "I would like the sex I have in real-life to be like the sex in pornography." Adopting a sexual script perspective (Wright & Bae, 2016), it could be argued that these findings indicate that pornography influences men's perceptions of what is normal and desirable within a sexual relationship. However, due to the correlational study design, it is not possible to rule out other explanations (e.g., preference for porn-like sex causing pornography use or this relationship being the result of an unmeasured third variable such as sexual liberalism).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a greater frequency of pornography use was predictive of greater agreement with the statement "I would like the sex I have in real-life to be like the sex in pornography." Adopting a sexual script perspective (Wright & Bae, 2016), it could be argued that these findings indicate that pornography influences men's perceptions of what is normal and desirable within a sexual relationship. However, due to the correlational study design, it is not possible to rule out other explanations (e.g., preference for porn-like sex causing pornography use or this relationship being the result of an unmeasured third variable such as sexual liberalism).…”
Section: Discussionmentioning
confidence: 97%
“…The basic position has been that reduced sexual satisfaction is likely if pornography consumers contrast the sexual attractiveness of their partners with actors in pornography, evaluate how their sexual encounters unfold against the positively planned and framed encounters depicted in pornography, and juxtapose their own and their partners' levels of bliss and elation postsex with the rapture and delight exhibited by pornographic performers (Stulhofer, Busko, & Landripet, 2010;Willoughby et al, 2016). The majority of this research has used the scripting concept heuristically, as opposed to testing particular tenets of theoretical models designed specifically to explain the effects of sexual media, such as the sexual script acquisition, activation, application model ( 3 AM; Wright, 2011Wright, , 2014Wright & Bae, 2016;Wright, Malamuth, & Donnerstein, 2012).…”
Section: Pornography and Interpersonal Satisfactionmentioning
confidence: 99%
“…Reasons cited were differential levels of pornography consumption, masturbation to pornography, acceptance of pornography, use of pornography for orientation validation, concern over body image, and ascriptions of masculinity to muscularity. Discussion of additional potential moderators can be found in Wright (2011Wright ( , 2014 and Wright and Bae (2016).…”
Section: Research Question 6: Publication Statusmentioning
confidence: 99%
“…However, individual characteristics and specific content have been found to moderate the strength of the association (Hald, Malamuth & Yuen, 2010;Malamuth, Addison & Koss, 2000;Malamuth, Hald & Koss, 2012;Vega & Malamuth, 2007;Wright, 2011). Wright et al (2016) identified a larger effect among those who watched violent pornography (r = .37, than those who reported non-violent pornography use (r = .26).…”
Section: Pornography Use and Sexual Aggressionmentioning
confidence: 95%
“…Due to its increased and unrestricted availability on the Internet, pornography use is a part of many adolescents' experience (Peter & Valkenburg, 2016). The rising prevalence of pornography use mostly, but not exclusively, among male adolescents prompted concerns among researchers and policy makers about the impact of pornography on youth sexual socialization-particularly regarding the acquisition of sexual scripts which may increase the risk of sexual aggression (Wright, 2011;Wright & Bae, 2016). A number of theories have been proposed to explain possible association between pornography use and sexual aggression.…”
Section: Introductionmentioning
confidence: 99%